THE RESULTS OF CLUSTER ANALYSIS OF UKRAINIAN REGIONS PROVISION BY PHARMACIES - Hala L. O. (World Science, 2019)
The results of regions` cluster analysis of the pharmacies in their total quantity in Ukraine from 2012 to 2019 have been presented. According to the objectives, five clusters have been built with different dynamics of years. Most regions were represented in the fourth cluster which consisted of 9 ones (37.5% of their total number). This cluster was characterized by a growing trend in indicators from 2012 to 2019. The most problematic from the socioeconomic point of view were the first (Lugansk) and third (Donetsk) regions, which, unlike all others, showed a sharp decrease of indicators in 2016 in comparison with other Ukrainian regions. The results obtained can be used for effective implementation of state regulation mechanisms in the retail pharmaceutical market of Ukraine.